2019
DOI: 10.1111/acer.14236
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Binge Drinking and Anxiety‐Like Behavior in Socialized Versus Isolated C57BL/6J Mice

Abstract: BackgroundBinge alcohol drinking has been characterized as a key feature of alcoholism. The drinking‐in‐the‐dark (DID) preclinical model, a procedure that promotes high levels of ethanol (EtOH) intake in short periods of time, has been extensively used to investigate neuropharmacological and genetic determinants of binge‐like EtOH consumption. Using DID methodology, alcohol‐preferring strains of mice such as C57BL/6J (B6) mice consume enough EtOH to achieve blood concentrations (≥1.0 mg/ml) associated with beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 67 publications
3
18
0
1
Order By: Relevance
“…Housing conditions during adolescence, but not adulthood, altered social and anxiety‐like behavior and not ethanol consumption (Rivera‐Irizarry et al., 2020). However, others have observed that mice single housed during adolescence did indeed increase ethanol consumption, which can be influenced by ethanol concentration, sex, and environmental enrichment conditions (Evans et al., 2020; Lopez & Laber, 2015). In the present work, adolescent mice were group housed until 2 days before the onset of the ethanol drinking paradigm.…”
Section: Discussionmentioning
confidence: 97%
“…Housing conditions during adolescence, but not adulthood, altered social and anxiety‐like behavior and not ethanol consumption (Rivera‐Irizarry et al., 2020). However, others have observed that mice single housed during adolescence did indeed increase ethanol consumption, which can be influenced by ethanol concentration, sex, and environmental enrichment conditions (Evans et al., 2020; Lopez & Laber, 2015). In the present work, adolescent mice were group housed until 2 days before the onset of the ethanol drinking paradigm.…”
Section: Discussionmentioning
confidence: 97%
“…In Drosophila , social isolation has been found to decrease synapse number in PDF neurons and reduce alcohol sensitivity [ 67 , 68 ]. Studies using rodent models have shown that social isolation increases alcohol preferences [ 141 , 142 , 143 , 144 ]. Therefore, we used a group-housed sleep deprivation method that significantly increased homeostatic sleep pressures in both male and females, as seen by increased sleep in the 36 h following the period of sleep deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, social isolation is known to induce profound behavioral and neurobiological alterations ( Mumtaz et al, 2018 ). Besides inducing anxiety and depressive-like behaviors in rodents ( Amiri et al, 2015 ), several studies pointed that isolation induces an increase in ethanol consumption in mice and rats ( Advani et al, 2007 ; Evans et al, 2020 ; Juárez and Vázquez-Cortés, 2003 ; Lopez et al, 2011 ; Sanna et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%